2001
DOI: 10.1046/j.1365-2648.2001.01952.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of work characteristics and reactions between general and mental health nurses: a multi‐sample analysis

Abstract: Regarding the differences in work characteristics and work reactions between mental health and general nurses, our hypotheses were confirmed, except for social support and job involvement. Autonomy and emotional exhaustion were higher among mental health nurses, whereas their job involvement proved to be significantly lower. Emotional exhaustion was primarily predicted by workload and lack of social support. Contrary to our expectations, the relationship between autonomy and job involvement was not significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
50
2
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 56 publications
0
50
2
1
Order By: Relevance
“…Studies indicate that in addition to stressful factors intrinsic to nursing, organizational and management attributes influence work-related stress among nurses (Stordeur et al, 2001;Makinen et al, 2003), and that sources of stress vary in both nature and frequency across nursing specialties (Siu, 2002;Tummers et al, 2001). Researchers have also concluded that occupational stress arises from social arrangements that are partially determined by the organization of work (Cooper, 1998) and from the interaction between these organizational factors and the characteristics of individual workers (Makinen et al, 2003).…”
mentioning
confidence: 99%
“…Studies indicate that in addition to stressful factors intrinsic to nursing, organizational and management attributes influence work-related stress among nurses (Stordeur et al, 2001;Makinen et al, 2003), and that sources of stress vary in both nature and frequency across nursing specialties (Siu, 2002;Tummers et al, 2001). Researchers have also concluded that occupational stress arises from social arrangements that are partially determined by the organization of work (Cooper, 1998) and from the interaction between these organizational factors and the characteristics of individual workers (Makinen et al, 2003).…”
mentioning
confidence: 99%
“…In hospital settings, there is some evidence to suggest differences in health and health behaviors between staff working in different specialties (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Studies of physicians show elevated rates of "burnout", mental disorders, substance use, and suicide among psychiatrists, anesthesiologists, and physicians working in emergency or primary care although the association is not robust (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14).…”
mentioning
confidence: 99%
“…Surgeons have also been shown to have higher (11) and lower (12) risk of death from ischemic heart disease when compared to other medical specialists. Studies of nurses suggest that psychiatric nurses report lower levels of work stress and burnout (15, 16) and higher levels of job autonomy (17) but also more emotional exhaustion Virtanen et al (17) than their collaborators working in non-psychiatric settings. No difference was found in one study investigating suicidal behavior among psychiatric healthcare personnel and the general population (18).…”
mentioning
confidence: 99%
“…In the workplace, this might involve latitude in how job tasks are completed, being rewarded for taking initiative, and feeling as though one's perspective is valued (Deci, Eghrari, Patrick, & Leone, 1994;Gagné & Deci, 2005). Past studies in samples of mental health providers have found that higher levels of workplace autonomy are negatively associated with burnout, particularly emotional exhaustion (Tummers, Janssen, Landeweerd, & Houkes, 2001;van Daalen, Willemsen, Sanders, & van Veldhoven, 2009). The second factor, competence, pertains to the need to feel capable of achieving desired outcomes (Baard, Deci, & Ryan, 2004).…”
mentioning
confidence: 99%
“…A work environment with high levels of staff cohesion, evidenced by trust and cooperation amongst staff members, would help fulfill the need for relatedness. Within the mental health sector, empirical studies have consistently demonstrated the value of social support and staff cohesion in protecting against burnout (Corrigan, Holmes, & Luchins, 1995;Tummers et al, 2001;van Daalen et al, 2009). Despite these promising findings, the relationships between perceived autonomy, competence (selfefficacy), relatedness (such as staff cohesion), and burnout have yet to be simultaneously studied in a sample of mental health providers.…”
mentioning
confidence: 99%